Banking Law Amendment as a Tool of Social Engineering - Christiani, Theresia Anita (European Scientific Journal, ESJ, 2018)
An amendment to law is a step in an effort to enable law for always following society development to meet the purpose of law. On the other hand, it is essential to study further whether existed draft of bank law already makes the law as a means of development. Problem formulations of this research are: first, what are the juridical factors causing banking law need to be amended immediately? and second, has the plan of banking law amendment design manifested the law as a tool of social engineering? This normative law research uses qualitative data analysis as the analysis technique. As the result, this research shows that : first, juridical factors causing Banking Law needs to be amended immediately are the importance of sharpening bank function both in micro and in macro in this case through the implementation of monetary policy and financial system stability and the importance of protection national interests through restriction of share ownership and synchronization of legislative regulations between Financial Services Authority Law and Banking Law about Financial Services authority in conducting management and supervision and second, plan of amendment on banking law always tries hard to adapt to the speed of economic development embodying law as a tool of social engineering .